Activity of copper and nickel loaded on HZSM-5 zeolite based catalyst for steam reforming of glycerol to hydrogen - Abdul Halim Yun, Hafizah (2013)
The study focuses on hydrogen production via glycerol steam reforming over copper and nickel loaded on HZSM-5 zeolite based catalyst. The catalysts were prepared by using different loading amount of copper (0-10wt%) and nickel (0-10wt%) on HZSM-5 zeolite catalysts through wet impregnation method and was characterized by X-Ray Diffraction (XRD). The performances of catalysts were evaluated in terms of glycerol conversion and hydrogen production at 500°C using 6:1 of water to glycerol molar ratio (WGMR) in a tubular fixed bed reactor. All the catalysts had achieved more than 85% of glycerol conversion except that of 5%Cu loaded on HZSM-5 catalyst. The addition of nickel into 5% Cu/HZSM-5 catalyst had increased the hydrogen yield. Similar trend was observed when copper was added into Ni/HZSM-5 catalyst but using copper loaded on HZSM-5 alone was unable to produce hydrogen compared to using nickel catalyst alone. It showed that copper acted as a promoter for hydrogen production. It was established that a 5wt% of Cu with 10wt% of Ni loaded on HZSM-5 catalyst showed significant improvement in terms of hydrogen yield and gaseous product compositions at selected operating conditions.